Yttrium chloride-modified Au/AC catalysts for acetylene hydrochlorination with improved activity and stability - Ke, Jinhuo; Zhao, Yuxin; Yin, Yan; Chen, Kun; Duan, Xinping; Ye, Linmin; Yuan, Youzhu (Journal of rare earths, 2017)
The addition of yttrium chloride （YC13） to an activated carbon-supported Au catalyst （AuIAC） canmarkedly promote the catalytic performance of acetylene hydrochlorination to the vinyl chloridemonomer （VCM）. The structure and physicochemical features of the YCl3-modified catalysts （Y-Au/AC）were measured by X-ray diffraction, X-ray photoelectron spectroscopy, temperature-programmedreduction, C2H2-temperature programmed desorption, and scanning transmission electron microscopy.The presence of YCI3 was found suppressing the reduction of highly oxidized Au^δ＋ （δ= 1, 3） to metallic Au^0 dependently and thus retard the agglomeration of Au nanoparticles during the reaction. In addition,the additive of YC13 to the Au/AC catalyst greatly inhibits the coke deposition on the catalyst surface. Theoptimized catalyst with an atomic ratio of Y/Au = 5 （1 wt% Au loading weight） yields an 87.8% acetyleneconversion and almost 100% selectivity for VCM under the reaction of GHSV（C2H2） = 800 h-1 at 180℃.The durability test indicates that the 5Y-1Au/AC catalyst maintains high catalytic activity for more than2300 h at 30 h-1 GHSV（C2H2） and 180℃, indicating great promise as a non-mercury catalyst for PVCmanufacture.